NILAI RELIGI DALAM NOVEL–NOVEL KARYA ASMA NADIA - Herni Tri Yuwana (LPPM UNISDA, 2018)
This study aims to describe the value of religion in the novel-novel by Asma Nadia covering aqidah, syariah, and morals. This research method using qualitative descriptive method. Research data is sourced from the novel